(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
The behavior of slurry-infiltrated fiber concrete (SIFCON) Vierendeel trusses under the applied load by employing numerical analyses for the studied trusses is the aim of this paper. The nonlinear behavior of such trusses have been investigated using the finite element software ABAQUS. A finite element model of three dimensions has been used. The structural behaviour is presented in terms of ultimate load, crack pattern and deflection. The numerical results show that the simulated numerical behavior has a good agreement with the experimental results of the pervious tested specimens and the failure mode similar to that recorded in the experimental test. It was found that when the openings are present, the usual flow of stresses is disrupted or interrupted, which causes stress concentration and early cracking in the area of the opening.